Strategi Penguatan Literasi di Sekolah - Joko Purwanto; Yuli Widiyono; Nurhidayati Nurhidayati; Ica Melvira Pratiwi; Lia Safira; Nurul Fitriani (Pelayanan Unggulan : Jurnal Pengabdian Masyarakat Terapan, 2024)
The development of technology and information is increasingly rapid. This of course requires the ability of students to face and anticipate it. One of the abilities that students must have is literacy. However, in fact, students in Indonesia still really need strengthening in the field of literacy. Various existing surveys show that these two capabilities have not experienced significant improvement. The same thing was also experienced by students at SMA Negeri 6 Purworejo. For this reason, a comprehensive and continuous effort is needed to improve this capability. Based on these situations and conditions, the Muhammadiyah University Purworejo Service Team built a collaboration with SMA Negeri 6 Purworejo to improve literacy skills for the school's residents. The theme raised was "Strengthening Literacy for Students, Teachers and Education Personnel at SMA Negeri 6 Purworejo". The activity begins with activity planning. Then, it continued with socialization activities and presentation of literacy strengthening strategies that could be carried out at the school. This activity was attended by approximately 300 students, 20 teachers and 12 education staff on October 25 2024 at the Outdoor High School 6 Purworejo. Strengthening strategies that must be implemented by SMA Negeri 6 Purworejo to strengthen literacy include: providing a literacy-friendly physical environment, getting used to reading 15 minutes before the first hour of learning begins, optimizing the role/function of the library, making visits to bookstores, optimizing corners. reading in every classroom, optimizing a school literacy team, and carrying out regular evaluations and follow-ups related to the literacy program that has been implemented.